The Influence of Information and Communication Technology On The Academic Achievement of Class B Office Administration Education Students in Unj 2022 - Natasya, Isma Syifa’a; Marsofiyati (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to analyze the influence of the use of information and communication technology on the academic achievement of class B Office Administration Education students at Jakarta State University (UNJ) in 2022. The research process involves collecting data through questionnaires which will be distributed to students. This research uses a quantitative approach with a methodology for descriptive and inferential data analysis. The research schedule includes preparation stages, data collection, data analysis, and reporting of results within one semester. Information and communications technology significantly improves students' academic performance, the study found. The significance of this research shows the importance of using information and communication technology into the learning process to improve academic outcomes